To Teach or Not to Teach? : Panel Data Evidence on the Quitting Decision - Stephen Wheatley Price; Michael A. Shields; Paul Frijters (Institute for the Study of Labor (IZA), 2004)
The question we address in this paper is which factors influence the quitting decision of public sector teachers in England and Wales, using a nationally representative panel data set over 1997-2003. We document the outcomes of former teachers, fit single and competingrisks duration models and examine the influence of relative pay on retention. Surprisingly, we find that teachers who move to outside employment earn 22% less pay, work longer hours, in largely nonprofessional occupations and mainly stay within the public sector. We estimate that a 10% increase in teachers? relative pay would reduce annual quitting rates by less than 1%.
Keywords: I18; J45; J63; 330; teachers; panel data; wages; quitting; Lehrkräfte; Arbeitsmobilität; Lohn; Schätzung; Grossbritannien